A conformationally adaptive macrocycle: conformational complexity and host–guest chemistry of zorb[4]arene - Yang, Liu-Pan; Lu, Song-Bo; Valkonen, Arto; Pan, Fangfang; Rissanen, Kari; Jiang, Wei (Beilstein Journal of Organic Chemistry, 2018)
Large amplitude conformational change is one of the features of biomolecular recognition and is also the basis for allosteric effects and signal transduction in functional biological systems. However, synthetic receptors with controllable conformational changes are rare. In this article, we present a thorough study on the host–guest chemistry of a conformationally adaptive macrocycle, namely per-O-ethoxyzorb[4]arene (ZB4). Similar to per-O-ethoxyoxatub[4]arene, ZB4 is capable of accommodating a wide range of organic cations. However, ZB4 does not show large amplitude conformational responses to the electronic substituents on the guests. Instead of a linear free-energy relationship, ZB4 follows a parabolic free-energy relationship. This is explained by invoking the influence of secondary C–H···O hydrogen bonds on the primary cation···π interactions based on the information obtained from four representative crystal structures. In addition, heat capacity changes (ΔCp) and enthalpy–entropy compensation phenomena both indicate that solvent reorganization is also involved during the binding. This research further deepens our understanding on the binding behavior of ZB4 and lays the basis for the construction of stimuli-responsive materials with ZB4 as a major component.
Keywords: conformations; host–guest chemistry; macrocycles; supramolecular chemistry; zorb[4]arene